TREN PENGHINDARAN PAJAK PERUSAHAAN MANUFAKTUR DI INDONESIA YANG TERDAFTAR DI BEI TAHUN 2001-2014 - Titiek Puji Astuti; Y Anni Aryani (Jurnal Akuntansi, 2016)
This study aims to determine the trend of tax avoidance manufacturing company in the long term. From the analysis of the trend of tax avoidance within relatively long period can be known how fluctuations in the increase or decrease in tax avoidance that occurs and what factors are influencing the increase or decrease in tax avoidance company so that tax authorities may evaluate policies issued in order to increase the level of taxpayer compliance. This research is a descriptive study using secondary data manufacturing company's financial statements from 2001 to 2014. The size of tax avoidance using ETR and CETR. The result is that the trend of corporate tax avoidance manufacturing high seen from the ETR and CETR small.